The Effectiveness of Behavioral Counseling to Reduce Student Learning Anxiety: Array - Taty Fauzi (Islamic Guidance and Counseling Journal, 2020)
This is a continuing study of a development behavioral model to help students reduce their learning anxiety. 192 students involved as study population after filled self-report scale of learning anxiety, but only 30 students who had meet the learning anxiety criteria and they were given counseling interventions. Through quasi-experiment pretest-posttest control group design, 30 students divided into two groups, 15 students in the experiment group with behavioral counseling and 15 students in the control group with no specific approach. Overall, there are significant differences between experiment and control group (t = -27.65, p < 0.05). The results of the proposed study prove that the behavioral counseling model showed higher impact to reduce learning anxiety rather than the conventional counseling with no specific approach. Therefore, the author concludes that behavioral counseling is one of the effective interventions to reduce students learning anxiety. The implication of this research to counseling practice will be discussed.